KESATUAN TEMA DALAM AL-QUR’AN (Telaah Historis-Metodologis Tafsir Maudhu’iy) - Muh Irfan Helmy (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2020)
The Maudhu'i interpretation method tries to present the Quran as a unified and inseparable unity. This method offers a solution through thematic discussion towards the content of the Quran. This article aims to reveal the dimensions of the unity of the themes in the Quran, the contribution of the Maudhu'i interpretation method as an alternative to the study of interpretation, and the urgency of the Maudhu'i interpretation method towards the Quran. Through the historicalmethodological approach, this article obtained the conclusion that a comprehensive perspective on the Quran is very urgent to be carried out so that the messages contained in the Qur'an can be picked up completely. The Quran is not only highlighted from one side which gives the impression that the Quran is only limited to the side that it highlights. The Maudhu'i interpretation method can be used as an alternative to the study of interpretation in realizing the ideal perspective on the Quran. However, the birth of the Maudhu'i method does not mean setting aside other methods. The elasticity of the study of Maudhu'i interpretation will continue to grow along with the times. The Maudhu'i interpretation method is not only limited to compiling verses but also mastery of all aspects required in the study of Quran interpretation.